Penerapan Model Pembelajaran Asuhan Nifas Terintegrasi Untuk Menciptakan Bidan yang Berkompeten Dalam Menjawab Kebutuhan Wanita - Hartiningtiyaswati, Setiya; Idjradinata, Ponpon; Husin, Farid (Infokes, 2017)
Objective: This study aims to analyze the effect of applying an integrated postpartum care learning model on the improvement of student competence. Design: This study used pre-post quasi-experimental design in the second years of midwifery student. Method Experimental group (n = 25) was given the integrated postpartum care learning model, while control group (n = 24) was given the conventional learning model (learning model that is normally used). Competency score was measured from a combination of knowledge, skill, and attitude related to postpartum. Result The result of the study showed that there were differences in the improvement of knowledge [control: mean (SD) = 2.19 (8.52); experimental = 5,9 (8.93)], attitude [control: mean (SD) = 18.15 (23.92); esperimental = 49.14 (20.96)], and skill [control: mean (SD) = 8.16 (19.17); experimental = 41.33 (19.53)] between control and experimental groups (p < 0.5). a combination of these scores showed there were signifcant differences in the improvement of competency between control and experimental groups (p < 0.05). Conclusion The integrated postpartum care learning model was better in improving student competence than the conventional learning model. It was a way to create a generation of competent midwives to meet the needs of women during postpartum.